Development and Validation of UV-Visible Spectrophotometric Method for Simultaneous Determination of Eperisone and Paracetamol in Solid Dosage Form - Shantaram Gajanan Khanage; Popat Baban Mohite; Sandeep Jadhav (Tabriz University of Medical Sciences, 2013)
Purpose: Eperisone Hydrochloride (EPE) is a potent new generation antispasmodic drug which is used in the treatment of moderate to severe pain in combination with Paracetamol (PAR). Both drugs are available in tablet dosage form in combination with a dose of 50 mg for EPE and 325 mg PAR respectively. Methods: The method is based upon Q-absorption ratio method for the simultaneous determination of the EPE and PAR. Absorption ratio method is used for the ratio of the absorption at two selected wavelength one of which is the iso-absorptive point and other being the λmax of one of the two components. EPE and PAR shows their iso-absorptive point at 260 nm in methanol, the second wavelength used is 249 nm which is the λmax of PAR in methanol. Results: The linearity was obtained in the concentration range of 5-25 μg/mL for EPE and 2-10 μg/mL for PAR. The proposed method was effectively applied to tablet dosage form for estimation of both drugs. The accuracy and reproducibility results are close to 100% with 2% RSD. Results of the analysis were validated statistically and found to be satisfactory. The results of proposed method have been validated as per ICH guidelines. Conclusion: A simple, precise and economical spectrophotometric method has been developed for the estimation of EPE and PAR in pharmaceutical formulation.